KARAKTER AGRONOMI BERBAGAI AKSESI TANAMAN KATUK (Sauropus androgynus (L.) Merr.) PADA PEMBERIAN BERBAGAI DOSIS URINE SAPI - Ekal Kurniawan; Arifah Rahayu; Yanyan Mulyaningsih (Universitas Djuanda Bogor, 2019)
Katuk (Sauropus androgynus (L.) Merr.) is an indigenous leafy vegetable whose growth is affectedby nitrogen element. This study was aimed at assessing the agronomic performance of four katukaccessions grown with various rates of cattle urine. A factorial completely randomized design wasused. The first factor was katuk accession consisting of four levels, namely Pandeglang, Cianjur,Sukabumi, Leuwiliang, and Kemang. The second factor was cattle urine rates consisting of 5 levels,namely 0%R cattle urine (0.0 ml/plant), 50%R cattle urine (468.75 ml/plant), 100%R cattle urine(937.50 ml/plant), 150% R cattle urine (1406.25 ml/plant), and 100%R urea (8.2 g/plant). Thegrowth and productivity of katuk of Cianjur accession had the highest number of buds, total lengthof buds, number of leaves, number of leaflets, fresh weight, and dry weight. The utilization of 50%R,100%R, and 150%R of cattle urine was found to have higher fresh and dry weight than did theutilization of 0%R cattle urine and 100%R urea. The best quality katuk was Cianjur accessionwhich was found to have the highest vitamin C and chlorophyll contents. No significant effects ofall treatments were found in all vegetative variables except plant height and root fresh and dryweight. It was concluded that cattle urine could be used as a urea substitute.Key words: Sauropus androgynus, number of buds, dry weight, indegenous plant